PHYSICAL TRAINING FOR PERFORMING MILITARY-APPLIED TASKS: PROBLEMS AND DEVELOPMENT PROSPECTS (Physical Culture and Sport: Scientific Perspective, 2025)
The article reveals the essence of physical training for performing military-applied tasks as a purposeful pedagogical process aimed at developing specialized physical readiness among future defense professionals. It has been established that professional-applied physical training ensures the development of a set of motor skills, psychophysical qualities, and functional capabilities that determine the effectiveness of performance under combat conditions. It has been clarified that the system of physical training encompasses an integrated set of objectives, including the development of physical abilities, the formation of psychophysical readiness, the acquisition of theoretical knowledge, and the cultivation of a need for self-improvement. It has been emphasized that the practical implementation of military-applied training involves performing exercises that are close to real combat conditions, such as forced marches, obstacle course overcoming, hand-to-hand combat, and casualty evacuation. It has been underlined that the development of modern methods of physical training requires the integration of training technologies, personalization of workloads, and the use of simulation systems. It has been stated that the effectiveness of physical training is determined by the combination of traditional and modern forms of exercise aimed at developing strength, endurance, coordination, and stress resistance. It has been determined that the formation of physical readiness constitutes a component of the overall system of combat training, ensuring the ability to operate effectively in complex environments. It has been noted that the further development of physical training requires the individualization of the training process, taking into account the physiological and psychological characteristics of trainees. The necessity of introducing personalized training programs, monitoring systems, and combat environment modeling has been emphasized. It has been generalized that the systematic improvement of military-applied physical training is a prerequisite for enhancing the professional competence and combat readiness of future specialists.
Keywords: physical training; military-applied tasks; programs; readiness; trainee; specialist